Leishmanicidal Activity and Ultrastructural Changes of Maslinic Acid Isolated from Hyptidendron canum - Adriana Jesus, Jéssica; Laurenti, Márcia Dalastra; Lopes Silva, Matheus; Ghilardi Lago, João Henrique; Domingues Passero, Luiz Felipe [UNESP] (Hindawi, 2021)
The therapeutic arsenal for the treatment of leishmaniasis is limited and has serious obstacles, such as variable activity, high toxicity, and costs. To overcome such limitations, it becomes urgent to characterize new bioactive molecules. Plants produce and accumulate different classes of bioactive compounds, and these molecules can be studied as a strategy to combat leishmaniasis. The study presented herein evaluated the leishmanicidal effect of maslinic acid isolated from the leaves of Hyptidendron canum (Lamiaceae) and investigated the morphological that occurred on Leishmania (Leishmania) infantum upon treatment. Maslinic acid was active and selective against promastigote and amastigote forms in a dose-dependent manner. Additionally, it was not toxic to peritoneal macrophages isolated from golden hamsters, while miltefosine and amphotericin B showed mild toxicity for macrophages. Morphological changes in promastigotes of L. (L.) infantum treated with maslinic acid were related to cytoplasmic degeneration, intense exocytic activity, and blebbing in the kDNA; disruption of mitochondrial cristae was observed in some parasites. The nucleus of promastigote forms seems to be degraded and the chromatin fragmented, suggesting that maslinic acid triggers programmed cell death. These results indicate that maslinic acid may be an interesting molecule to develop new classes of drugs against leishmaniasis.